SINTESIS KOMPOSIT SELULOSA SERBUK GERGAJI KAYU KAMPER-LIMBAH PLASTIK LDPE (LOW DENSITY POLIETHYLENE) DENGAN REAGEN FENTON SEBAGAI AGEN PENGKOPLING - Hudi Nurwendi; I Nengah Simpen; I Made Sutha Negara (Jurnal Kimia (Journal of Chemistry), 2016)
This research was on the synthesis of cellulose composites from camphor wood sawdust with LDPE waste (cellulose-LDPE) and Fenton reagent (H2O2/Fe2+) as the coupling agent. This study was divided into three steps: preparation, variation of LDPE composition and H2O2 concentration, and characterization. Preparation was done with cellulose extraction of sawdust and LDPE plastic waste purification. Variation was performed to determine the effect of compositions of LDPE on composites celullose-LDPE and H2O2 concentration on Fenton reagent. Characterization was done by testing the physical properties and functional groups using FTIR analysis. The best values of the physical property were obtained from cellulose-LDPE composition ratio of 1:5 on 1.5% H2O2. These were MOE (Modulus of Elasticity) of 12.71 MPa, MOR (Modulus of Rupture) of 200.24 MPa and density of 0.7936 g/cm. FTIR analysis showed the higher the composition of LDPE, the higher the wavenumber for OH and the increase of H2O2 concentration increased the C-H wavenumber functional groups.